The Community Efforts iIn Preserving the Coral Reef Ecosystem in Sabang City - Azis, Daska; Murtisal, Eva (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
This study aims to know how the efforts of Sabang City community in maintaining and preserving the coral reef ecosystem in Iboih, Sabang City. The study was conducted in 2017, data collection techniques were using documentary studies, observations, questionnaires and in-depth interviews descriptively related to the efforts that have been done in the conservation of coral reef ecosystems. The data analysis shows that most (98.22%) of the respondents' answers have made efforts in maintaining and preserving the coral reef ecosystem in Iboih Sabang City. The role of communities greatly determines the success in managing the conservation of natural resources of coral reef ecosystems in coastal areas by empowering or raising awareness and understanding to convince coastal communities for long-term benefits of coastal protection as key to sustainable development.